High-rate roll-to-roll stack and lamination of multilayer structured membrane electrode assembly. (August 2016) - Chen, Jiankui; Liu, Huimin; Huang, YongAn; Yin, Zhouping
Highlights: The roll-to-roll seal lamination equipment is integrated into whole manufacturing equipment, and all functional modules work in good condition. The manufacturing system can address the issue of collaboration between discontinuous die-cutting process and continuous peeling and lamination processes. Abstract: A membrane electrode assembly (MEA) is the heart of a proton exchange membrane (PEM) fuel cell stack. The presented roll-to-roll (R2R) system is initially developed for the mass production of MEA with high alignment precision, to avoid time-consuming manual manipulation. It is challenging to align large-area flexible multilayer structured membranes precisely. Two trilayer seal membranes are half-die-cut to structured films with various numbers of layers when their upper 2-layers are peeled off. Then the two structured trilayer seal films are laminated with skinless PEM to form composite PEM. In order to guarantee the manipulation precision and the registration of several multilayer structured films, the dark field illumination device and contact measurement device are developed to detect the micro-scale indentation on the transparent film. It can guarantee the discontinuous die-cutting process collaborates with the continuous R2R peeling and lamination processes, in a controllable production rhythm. The R2R technology is highly scalable for large area fuel cells.